Restriction Enzymes in Microbiology, Biotechnology and Biochemistry (Encuentro, 2012)
Since their discovery in the nineteen-seventies, a collection of simple enzymes termed Type II restriction endonucleases, made by microbes to ward off viral infections, have transformed molecular biology, spawned the multi-billion dollar Biotechnology industry, and yielded fundamental insights into the biochemistry of life, health and disease. In this article we describe how these enzymes were discovered, and we review their properties, organizations and genetics. We summarize current ideas about the mechanism underlying their remarkable ability to recognize and bind to specific base pair sequences in DNA, and we discuss why these ideas might not be correct.We conclude by proposing an alternative explanation for sequence-recognition that resolves certain inconsistencies and provides, in our view, a more satisfactory account of the mechanism.